Health attitudes and suicidal ideation among university students. Issue 3 (2nd April 2016) - Ashrafioun, Lisham; Bonar, Erin; Conner, Kenneth R.
ABSTRACT: Objective : The purpose of this study was to examine whether positive health attitudes are associated with suicidal ideation among university students after accounting for other health risk factors linked to suicidal ideation.Participants : Participants were 690 undergraduates from a large midwestern university during fall semester 2011.Methods : Participants reported demographics and health characteristics. Regression models compared individuals who reported suicidal ideation and those who did not.Results : In unadjusted models, suicidal ideation was significantly negatively associated with positive health attitudes, and positively associated with depression, drug use problems, sleep problems, and being overweight. In adjusted models, more positive health attitudes continued to be significantly negatively associated with suicidal ideation.Conclusions : This study suggests a link between positive health attitudes and lower probability of suicidal ideation. Additional research is needed to assess enhancing general health attitudes as a suicide prevention effort.